Effectiveness Of Literacy And Numeracy Drive On The Quality Of Primary Education - Ramsha Khurshid , Muhammad Javed , Qurat-ul-Ain (Migration Letters, 2024)
Literacy and Numeracy Drive (LND) is an application that is designed to boost and enhance the literacy and numeracy skills of primary level students. With reference to LND application, it consists of seven objective type questions of English, Urdu and Mathematics for class three. This study aims at identifying the purpose, use, effectiveness, benefits, role and positive impact of LND on the quality of primary education that is used by students, guided by their teachers and Assistant Education Officers (AEOs) to acquire basic literacy and numera[1]cy skills. The target population was teachers teaching to class three students studying at public sector primary, elementary and secondary schools and AEOs of Tehsil Bahawalpur, Pakistan. Two hundred and two (202) primary school teachers and thirty five (35) AEOs from Bahawalpur City and Saddar were selected through convenient sampling. A questionnaire consisting of the items related to the use, effectiveness, benefits and impact of using LND application was developed by the researchers to collect data. The data were analyzed through descriptive statistics to determine the frequency, ANOVA and T- Test. The findings based on the quantitative analysis of data, revealed that LND is an effective application to enhance literacy and numeracy skills of primary students as it promotes conceptual learning. The results also indicate that the students enjoy learning. The students face difficulty mostly in the subject of English particularly in reading comprehension. There are still some issues regarding the use and the fear of poor results of teachers and AEOs. Therefore, the researchers suggest that more attention should be paid on English subject. Special LND classes should be arranged on daily basis in order to improve the students’ learning. It will also be helpful to reduce the fear of teachers and AEOs regarding students’ results.